High unhealthy food and beverage consumption is associated with poor diet quality among 12–35-month-olds in Guédiawaye Department, Senegal - Vanderkooy, Anna; Ferguson, Elaine L.; Sy, Ndèye Yaga; Kane, Rosenette; Diagne, Maty; Mbodji, Aminata; Pries, Alissa M. (Frontiers in Nutrition, 2023)
Background: High consumption of unhealthy foods and beverages (UFB) during early childhood is cause for concern, with growing evidence from low- and middle-income countries finding associations with poor diet quality and malnutrition. Research from sub-Saharan Africa remains limited, with no studies quantifying the contribution of UFB to total energy intakes (TEI) among young children or exploring the relationship between such intakes and diet quality or anthropometric outcomes. Objectives: Assess UFB consumption patterns and their contribution to total energy intake from non-breastmilk foods/beverages (TEI-NBF), assess the association between high UFB consumption and dietary/nutrition outcomes, and explore drivers of unhealthy food choice among young children in Guédiawaye Department, Senegal. Methods: We conducted a cross-sectional study of a representative sample of 724 primary caregivers and their 12-35.9-month-old children. The study included a questionnaire, a quantitative four-pass 24-hour dietary recall, and anthropometric measurements. The contribution of UFB to TEI-NBF was calculated and terciles generated. Logistic and linear models were used to compare outcomes of high versus low UFB consumption terciles. Results: UFB contributed on average 22.2% of TEI-NBF, averaging 5.9% for the lowest tercile and 39.9% for the highest. Diets of high UFB consumers, as compared to low, were significantly less dense in protein, fiber, and seven of the 11 micronutrients assessed and significantly denser in total fat, saturated fat, and total sugar. No associations were found with anthropometric outcomes. High UFB consumers were older and more likely to be living in food insecurity. The most common drivers of commercial UFB consumption were related to child preference, the use of these products as behavior management tools, treats, or gifts, and the sharing of these products by someone else eating them. Conclusion: High UFB consumption is associated with poor diet quality among 12–35-month-olds in Guédiawaye Department, Senegal. Addressing high UFB consumption during this critical developmental period should be prioritized in young child nutrition research, programming, and policy development.